Determination of salmonella spp. presence and antibiotic resistance in egg and egg products - Hilal Keskinoğlu; Göknur Terzi Gülel (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine the presence of Salmonella spp. in egg and egg products and to determine antibiotic resistance profiles and minimum inhibitory concentration (MIC) values of isolates. Materials and Methods: A total of 200 samples including 100 eggs (35 village eggs, 35 conventional eggs and 30 organic eggs) and 100 egg products (30 egg powders, 70 pasteurized liquid eggs) were collected from Samsun, Turkey. Eggshell and egg contents samples were processed separately by pooling three eggs together. The isolation and identification of Salmonella spp. was done according to the method proposed by ISO 6579. The antimicrobial susceptibility of Salmonella spp. isolates to various antibiotics and MIC values was performed by VITEK 2 compact system using VITEK 2 AST-GN38 cards. Results: Salmonella spp. were found in two of 100 (2%) eggs (organic egg contents) and one of 100 (1%) egg products (pasteurized liquid egg). A total of 11 isolates were confirmed by PCR techniques as Salmonella spp. with the presence of oriC gene. The highest resistance was against amikacin, enrofloxacin, gentamicin, tobramycin, cephalexin (100%), followed by nitrofurantoin (81.8%), tetracycline (63.6%), ampicillin (54.5%), piperacillin (54.5%), cefpodoxime (54.5%), and imipenem (9.09%). However, there was no resistance to amoxicillin, marbofloxacin and trimethoprim/sulfamethoxazole. The results showed that 11/11 (100%) of Salmonella spp. from three sample showed multi-drug resistance against three or more antibiotic agents. Conclusion: It is recommended to implement good hygiene practices, good production practices and pasteurization techniques to minimize the risk of Salmonellosis due to the consumption of eggs and egg products.